Local Government Internal Audit Quality: Input Factors, Individual Level (Study on Inspectorate Auditors in North Sulawesi Province) - Meidy Kantohe; Frida Magda Sumual (Jurnal Ilmiah Akuntansi, 2024)
The quality of local government internal audit is very important in realizing good governance and clean government. This study aims to provide empirical evidence regarding the effect of Communication Skills, Professional Commitment and Self-Efficacy on Local Government Internal Audit Quality and the role of self-efficacy in mediating the effect of professional commitment on local government internal audit quality. This research is explanatory research with a survey approach and uses the census method. The study was conducted on 220 Inspectorate auditors at 16 Inspectorates in North Sulawesi Province. The data collection technique used a questionnaire made using google form. The results showed that the higher the communication skills, professional commitment and self-efficacy, the better the quality of internal audit. Self-efficacy mediates the effect of professional commitment on internal audit quality.